Group portrait of employees at plant for the California Packing Corporation - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of the employees of a California Packing Corporation packing plant. Behind the employees are numerous boxes labeled "C.P.C. No.1." These objects indicate the packing house depicted is probably plant #1 for the California Packing Corporation. The agricultural product under process is uncertain.